Skill or luck? analysing random influences on goal scoring in football - Wunderlich, F.; Seck, A.; Memmert, D. (13th World Congress of Performance Analysis of Sport and 13th International Symposium on Computer Science in Sport. IACSS&ISPAS 2022, 2023)
The number of goals is the only measure deciding on success in football. Consequently, a whole literature strand in performance analysis is concerned with identifying systematic strategies, that promise higher chances to score goals. At the same time, research concerned with forecasting or statistical modelling of football highlights the significant amount of unsystematic influences contributing to match results. Thus, it seems plausible to assume that besides systematic effects, goal scoring might be significantly influenced by random contributions. Surprisingly, there is hardly any research so far that investiges random contributions in goal scoring directly by means of match events. The results presented here are based on more than 7 000 goals from the Premier League, which were systematically checked for random contributions. The analysis finds that almost one in two goals is subject to random influence, that the degree of randomness involved is influenced by situational variables and, in particular, the degree of randomness has decreased over the last years.